Mechanical properties and drug release rate of poly(vinyl alcohol)/poly(ethylene glycol)/clay nanocomposite hydrogels: Correlation with structure and physical properties. Issue 32 (15th April 2019) - Ghanaatian, Effat; Entezam, Mehdi
ABSTRACT: Poly(vinyl alcohol)/poly(ethylene glycol) hydrogels containing curcumin as a drug and the various amounts of a montmorillonite nanoclay are prepared using the freezing–thawing method. Nanoclay quantity influence on the physicomechanical properties and the drug release rate of the hydrogel as well as relationship between them is investigated. X‐Ray diffraction and Atomic force microscopy analysis reveal the nanoclays have an intercalation structure in the hydrogel, and the hydrogel crystallization decreases with increasing the nanoclay inclusion. From the SEM micrographs observation, it was revealed that due to the presence of the nanoclay in the hydrogel, its porosity decreased. The naonoclay has an amount‐depended dual effect on the hydrogel swelling. The swelling mechanism is a normal Fickian diffusion for all the hydrogel samples. Strong physical interactions between the nanoclays and the polymer chains in the nanocomposite hydrogels are evidenced by the rheological studies. These interactions lead to significant reinforcement of the hydrogel tensile strength, intensified by the nanoclay amount. Interestingly, the nanoclays show the capability of accelerating and, also, decelerating the drug release of the hydrogel. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47843. Abstract :